Ultimate behaviour of reinforced concrete shear walls with octagonal openings - Hatami, Somaieh (2015)
Reinforced concrete shear wall is an in-plane vertical structural component with an ability to resist both the gravity and lateral forces. It has a good behaviour in resisting the building structures in earthquakes. In tall buildings layout, shear wall configuration generally makes access difficult to the public areas at the base or other floor levels such as the car park area and the entrance to the lifts or staircases. This can be solved by providing an opening in the shear wall structures. Shear walls that is perforated with openings are called coupled walls. The number, location and size of openings are directly affect the behaviour of the shear walls and cause to decrease the strength and stiffness of the structure. This study proposes adding haunches to the corners of rectangular opening as a method of strengthening the shear walls. In order to evaluate the behaviour of the shear wall structure in the presence of haunches, five small scale models of reinforced concrete shear walls with different arrangements of rectangular and octagonal openings were tested under a cyclic static horizontal point load at the top of the structure. Furthermore, theoretical method based on strain compatibility approach and the Total Moment Concept and Nonlinear Finite Element Analysis (NLFEA) with the aid of ABAQUS software have been performed to detailed study and verify the experimental outputs. A simple analytical equation has been proposed to calculate the maximum displacement of shear walls by considering the effective stiffness of cracked sections of shear wall components. The results demonstrated that the haunches caused a delay to the formation of cracks and increased the capacity of coupling beams and enhanced the ultimate strength and stiffness of shear wall structures. The accuracy of suggested maximum displacement equation was assessed and concluded that the results were in good agreement with experiment.